A qualitative overview of capacitive sensing techniques for two phase flow measurement - Tasnim, R.; Khan, Sheroz; Mohamed, Musse; Arshad, A.; Saquib, N. (IEEE, 2012)
The significance for measuring the accurate flow rate of gases in pipelines has been ever-increasing in the industrialized regions. There arises the need for gross measurements of gas-flow at some points while more accurate measurements of gas-flow are needed at some other points in an industry. Moreover, as the industry develops it undergoes changes for more comfortable user friendly way of gas flow measurement with improved accuracy. This is coupled with research activities catching demands for exploring alternative and non-invasive means of electronic measurement, thus putting into research more of a precise and reliable measurement rather than just measurement. Various contact and noncontact techniques are available currently for measuring the mass flow rate, pressure, concentration, mean flow velocity and also some other electrical and mechanical parameters in the single, two-and multiphase flows. This paper presents the recent development of noncontact non-contact capacitive flow measurement sensing techniques for two phase flow along with its several noteworthy aspects. The methods employed by some researchers are scrutinized and some measurement parameters are suggested to be optimized in a noteworthy level for future implementation.